Economic Dispatch Analysis of Risk Prevention and Control Based on Game Theory Equilibrium - Qixiang WANG; Zhentao HAN; Yi LIANG (Zhongguo dianli)
To evaluate the costs and benefits of each power generation and consumption entity in the power system, it is necessary to analyze the game theory equilibrium point of the economic dispatch problem. With the massive integration of renewable energy units and the gradual improvement of users' awareness of green power consumption, both the generation and consumption sides of the power system are showing new characteristics. First of all, the low marginal cost characteristics of renewable energy units, the need for risk prevention and control of system operation, and users' demand for green power will all have an impact on the mathematical form of the economic dispatch problem. At the same time, traditional analytical methods also face problems such as numerous variables and difficulty in solving nonlinear equilibrium problems. In order to solve these problems, this paper first proposes an economic dispatch mathematical model for risk prevention and control of the power system considering green power generation and consumption and then puts forward a game theory equilibrium solution algorithm based on the optimal response method. Through case analysis, the game theory equilibrium situation of the economic dispatch problem under the generation and consumption of renewable energy is evaluated, and relevant suggestions are put forward for investment planning on the power generation side of the power system.